Summer of my German soldier - Greene, Bette 1934- (New York, N.Y. Dial Books, 1973)
When German prisoners of war are brought to her Arkansas town during World War II, twelve-year-old Patty, a Jewish girl, befriends one of them and must deal with the consequences of that friendship.
Keywords: World War, 1939-1945 -- Arkansas -- Juvenile fiction; World War, 1939-1945 -- United States -- Fiction; Conduct of life -- Fiction; Prisoners of war -- Fiction; Self-esteem -- Fiction; Prejudices -- Fiction; Jews -- United States -- Fiction; Arkansas -- History -- 20th century -- Fiction